Influence of Nutritional Intake and Fe supplements in Adolescent Girls in Urban and Rural Areas in terms of Anemia Incidences - Pascoal, Meildy E.; Kereh, Gabriela C.; Harikedua, Vera T.; Tomastola, Yohanis; Ranti, Irza N.; Kereh, Phembriah S.; Otoluwa, Fitri M.; Montol, Ana B. (Disease and Health Research: New Insights Vol. 3, 2024)
Backgrounds: Globally, Iron Deficiency Anemia is the most common nutritional problem, affecting approximately 2 billion people worldwide, the majority (89%) of whom live in developing countries. Iron nutritional Anemia is anemia that arises due to empty iron reserves in the body so that the formation of hemoglobin is disrupted. Hemoglobin is part of red blood cells used to determine anemia status. Decreased iron intake can reduce hemoglobin levels in the body. Aim: The purpose of the study was to determine food intake and consumption of blood supplement tablets (Fe) on the incidence of anemia among adolescent girls in Urban and Rural areas. Methods: This type of research is Experimental Research using Quasi-Experimental design. This research was carried out at SMP Negeri 3 Manado and SMP Kristen Koha after obtaining approval from the ethics commission in August-September 2023. The population in this study were adolescent girls in SMP Negeri 3 Manado and SMP Kristen Koha. The sample in this study was obtained by estimating the difference between two population proportions with an absolute precision formula totaling 88 students divided into 44 adolescent girls in urban areas and 44 adolescent girls in rural areas. Univariate and Bivariate analyses were carried out. The analysis in this study was carried out using the Independent t-test to analyze differences in nutritional intake and consumption of Fe tablets on the incidence of anemia in urban and rural adolescent girls with the criterion of p <0.05. Results: School-aged children may be at risk of developing health problems during their growth and development. This study indicates that there is a difference in the average hemoglobin levels of adolescent girls in State Junior High School 3 Manado and Kristen Koha with a value of p<0.005, there is a difference in the average food intake (energy) of adolescent girls State Junior High School 3 Manado and Kristen Koha with a value of p<0.005, there is a difference in the average consumption of Fe tablets of adolescent girls in State Junior High School 3 Manado and Kristen Koha with a value of p<0.005. This study also stated that the need for micronutrients is small in the body but its role is very large for the functional body. Conclusion: The conclusion of this study is that there is a difference in the average hemoglobin levels of urban and rural adolescent girls with p<0.005, there is a difference in the average food intake (energy) of urban and rural adolescent girls p<0.001, and there is a difference in the average consumption of Fe tablets of urban and rural adolescent girls with p<0.004.